Identifying the Dimensions of Leadership Effectiveness of Farhangian University Campus Principals - Meydani, Mahmoud; Ghorchian, Nadergholi; Jafari , Parivash; Zamani Moghadam, Afsaneh (Iranian Journal of Educational Sociology, 2022)
Purpose: The aim of this study was to "identify the dimensions of leadership effectiveness of Farhangian University campus principals."Methodology: This research was exploratory in terms of applied purpose, in terms of field implementation method and in terms of data collection method. The statistical population of this study consisted of full-time and part-time faculty members of Farhangian University campuses in the academic year of 2018-19, who were selected and studied by random sampling of relative classes. A researcher-made questionnaire was used to collect information and exploratory factor analysis method was used to analyze the collected data.Findings: The results indicate the recognition of the dimensions of leadership effectiveness of Farhangian University campus managers in three dimensions: 1. Perceptual (personal) evaluation (others' perception of the leader's credibility and self-assessments; Peers, and superiors inside and outside the organization do training, create indicators of effectiveness), 2. Satisfaction of subordinates (individual) (Satisfaction of members of the organization) and 3. Achievement of organizational goals (relative levels) Achieving the goals of the organization) was in the form of 30 indicators.Conclusion: In order to achieve its goals and aspirations, Farhangian University should constantly evaluate the performance of its campus administrators based on the dimensions of perceptual evaluation, subordinates' satisfaction and achievement of organizational goals, review the processes and change the patterns and structures. Achieves higher effectiveness.